La biophotonique au service de l'identification de marqueurs pronostiques intracellulaires - Klossa, Jacques; Daliphard, Sylvie; Toussard, Xavier; Veilh, Philippe; Manfait, Michel; Angulo, Jesus; Flandrin, Georges; Beljebbar, Abdelilah; Untereiner, Valérie; Happillon, Teddy; Gobinet, Cyril; Velasco-Forero, Santiago; et al. (Ingénierie et recherche biomédicale, 2011)
Using biophotonics techniques to retrieve prognostic intracellular signatures : IHMO project aims at developing a multimodal microscopy platform that includes in a single machine Raman micro spectroscopy and multispectral imaging used for tumor diagnosis and prognosis. Lymphocytes from 24 leukaemic patients suffering from hyper leukocytosis Chronic Lymphoid Leukemia and from 11 healthy individual have been studied, using around 90 cells per blood sample. Blood smears were prepared on microscopy slides; cells were localized by optical microscopy, and Raman microspectroscopy spectra were acquired on cell nuclei. Afterward multi-Z stacks images of each cell were acquired for eight bands distributed in the visible spectrum. Raman data's were classified using a Support Vector Machine algorithm that provided a molecular signature that allowed for distinguishing lymphocytes from other nucleated blood components with 99.6% sensibility and 98.8% specificity. Then the algorithm was used for developing a classification model splitting leukaemic and healthy smears; sensibility was 95% and specificity was 87.5% among the spectra used for evaluation: 1540 from 11 leukaemic patients and 516 from seven healthy individual. IHMO project has demonstrated the power of Raman microspectroscopy for cell classification. Morphological descriptors obtained from multi-Z and multispectral images provide another independent classification that still needs to be assessed. The microscopy platform can be used more generally in the field of cytohaematology, however application to cytological and histological pathology would need further developments.